To What Extent Does Posthospital Discharge Chemoprophylaxis Prevent Venous Thromboembolism After Bariatric Surgery?: Results From a Nationwide Cohort of More Than 110, 000 Patients. Issue 4 (April 2018) - Thereaux, Jérémie; Lesuffleur, Thomas; Czernichow, Sébastien; Basdevant, Arnaud; Msika, Simon; Nocca, David; Millat, Bertrand; Fagot-Campagna, Anne
Abstract : Objective: The aim of the present study was to assess the incidence, risk factors, and the impact of posthospital discharge (PHD) chemoprophylaxis on venous thromboembolism (VTE) in patients undergoing bariatric surgery (BS). Background: VTE is a major concern after BS, especially during the PHD period. No large-scale study has previously focused on the clinical value of PHD chemoprophylaxis. Methods: In this nationwide observational population-based cohort study, all data from patients undergoing BS were extracted from the French National Health Insurance database (SNIIRAM) from 1st January 2012 to 31st September 2014. Logistic regression models were used to compute odds ratios for potential risk factors for VTE occurring within 90 postoperative days (PODs). The association between use of PHD chemoprophylaxis (heparin) and VTE was also assessed. Results: The majority (56%) of the 110, 824 patients had sleeve gastrectomy. VTE rates during the first 30 and 90 PODs were 0.34% and 0.51%, respectively. On multivariate analyses, the major risk factors for VTE during the first 90 PODs were history of VTE [odds ratio = 6.33 95% confidence interval (4.44–9.00)], postoperative complications [9.23 (7.30–11.70)], heart failure [2.45 (1.48–4.06)], and open surgery [2.38 (1.59–3.45)]. PHD chemoprophylaxis was delivered to 75% of patients. No use of PHD chemoprophylaxis [1.27 (1.01–1.61)] was an independent predictive factor of VTE during the first 90 PODs [in the gastric bypass group: 1.51 (1.01–2.29)). Conclusions: In the modern era of BS, this nationwide study shows a non-negligible rate of VTE especially after sleeve gastrectomy, depending on the individual risk level. Use of PHD chemoprophylaxis may decrease the risk of PHD VTE. Abstract : Supplemental Digital Content is available in the text